New DNA motifs : structure and potential activity against HIV and cancer - Do, Ngoc Quang (2012)
Guanine-rich oligonucleotides have the ability to adopt non-canonical structures, called G-quadruplexes. G-quadruplex structures are highly polymorphic, depending on their sequences and environmental conditions. In this thesis, we study structural features of G-quadruplexes adopted by oligonucleotides, that are known to possess activity against HIV-1 integrase and cancer.